2018
DOI: 10.5505/megaron.2017.97658
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Social Belonging, Displacement and Social Exclusion in the Neighborhood: Urban Redevelopment in Sarigol, Istanbul, Turkey

Abstract: İlkim MARKOÇ, Candan ÇINARKentsel dönüşüm en çok gecekondu alanlarında gerçekleşmektedir. Bu süreçten en çok etkilenen grup ise gecekondululardır. Kentsel dönüşüm projeleri, mahallenin sosyal dokusunda değişime sebep olmasından dolayı pek çok sorunu beraberinde getirmektedir. Bu makalenin amacı, İstanbul'da bir dönüşüm alanı olan Sarıgöl'deki süreçte ortaya çıkan sorunları aidiyet kaybı, yerinden edilme ve sosyal dışlanma kavramları bağlamında ele almaktır. Bir çok çalışmaya göre sosyal dışlanma, aidiyet duygu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…If so, social disarticulation has long term impact on the displaced people which need the attention of government before making decision for relocating people from their original location. This nding is consistent with the research ndings of (Aboda et al, 2019;Ambaye & Abeliene, 2015; M. M. Cernea, 2009;Ejigu & Abraha, 2018;Hussen & Kibret, 2018;Yuqi Liu et al, 2017;Markoç & Çinar, 2018;Nikuze et al, 2019). social network of the households before making decision to displace them and try to resettle them together per their previous relationships.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…If so, social disarticulation has long term impact on the displaced people which need the attention of government before making decision for relocating people from their original location. This nding is consistent with the research ndings of (Aboda et al, 2019;Ambaye & Abeliene, 2015; M. M. Cernea, 2009;Ejigu & Abraha, 2018;Hussen & Kibret, 2018;Yuqi Liu et al, 2017;Markoç & Çinar, 2018;Nikuze et al, 2019). social network of the households before making decision to displace them and try to resettle them together per their previous relationships.…”
Section: Discussionsupporting
confidence: 88%
“…According to Yuqi Liu et al (2017) urban redevelopment generally leads to the reconstruction of the built environment and the relocation of original residents, which leads to substantial weakening of existing neighborhood attachment and neighborly relationships. For example, a survey carried out in Sarigol, Istanbul, Turkey indicated that those forced to relocate due to urban regeneration projects had little attachment to their new neighborhoods and suffered from the loss of their original social ties (Markoç & Çinar, 2018). Another survey conducted in Guangzhou, China showed that those who moved back to their previous neighborhoods after redevelopment suffered from a sense of disorientation and isolation (Yuqi Liu et al, 2017).…”
Section: Literature Review: Concepts Of Urban Redevelopment and Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…The motives behind practices of social exclusion as well as the outcomes differ according to time, space and social structures of societies and thus, both dimensions can be studied under different theoretical basis. In literature, the processes/practices of social exclusion are mostly discussed in 4 forms: economic, spatial, cultural and political (Adaman ve Keyder, 2006;Apăteanu and Tatar, 2017;Barnes, 2002;Dufy, 1995;Markoç and Çınar, 2018;Sapancalı, 2003).…”
Section: Rethinking Social Justice Social Exclusion and Integration mentioning
confidence: 99%